Prediction of the surface cracking pattern of an oxidized polymer induced by residual and bending stresses. (August 2016) - Leguillon, D.; Lafarie-Frenot, M.C.; Pannier, Y.; Martin, E.
Abstract: The objective of the paper is to analyse four point bending tests performed on samples of an epoxy-type thermoset polymer oxidized under several conditions, and to predict the failure mechanisms. Different responses are observed depending on the oxidation time: for small durations there is a linear elastic phase followed by an abrupt failure of the specimen whereas for higher oxidation times, the elastic phase is followed by a nonlinear one corresponding to the development of numerous superficial micro-cracks prior to failure. In order to predict this behaviour, a finite fracture mechanics approach based on the coupled criterion is used. This criterion requires energy and stress conditions to be fulfilled. This approach is here extended to take into account the gradient of properties of the oxidized layer: Young's modulus, tensile strength, toughness. One novelty of the approach is to implement the model in a periodic representative cell in order to process an increasing number of cracks. Despite the large scattering in the experimental detection of the initiation of the micro-cracks and their counting, the predictions agree rather well with the observations: the oxidation times leading either to a sudden failure of the sample or to micro-cracking are well reproduced, and the loads triggering the crack onset as well as the increase in number of cracks are somewhat well predicted.